KINERJA BIDAN PEMBINA WILAYAH PUSKESMAS - Aisyah Aisyah; Sugeng Riyani (Jurnal Ilmu dan Teknologi Kesehatan, 2013)
In Kabupaten Bekasi infant mortality rate in the year 2010 is 41,17/1000. The maternal mortality rate is 34 cases and Standard Minimum Service not yet show results in optimal where out of 39 Puskesmas there are 29 Puskesmas not reached target. This signifies that the performance of supervisor midwife is less. Therefore this research aims to know the factors that relate to the performance of supervisor midwives. The designof research is crossectional by making use of primary data. The collection of data by spreading questioner to 39. Supervisor midwives. The result of the research found that the performance of a midwife who gets good 26,3 %, and the performance of midwife who gets less 73,7%, less performance of midwife may be caused by too many problem such as high task and high responsibility of a midwife. Variable meaningful namely long work with the results of P value 0.025 and value OR= 8,44. It means that long experience of midwife has chance 8,44 times than shorter midwife experience. The productivity of long experience midwife is usually much more than new experience. According to Stafen R, Robin (1996) there is not insurance between experience of new and long experience.